URGENSI DIGITALISASI PENDIDIKAN SEKOLAH - Cut Nelga Isma; Rina Rahmi; Hanifuddin Jamin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
The development of the digital world is happening so dynamically, sooner or later it not only affects but changes people's lifestyles which cannot be avoided. For this reason, this article aims to examine the urgency of digitizing school education in the face of the 4.0 to 5.0 revolution era. This research uses descriptive qualitative research with a literature review method. The data collection technique uses the Content Analysis method obtained from various sources including scientific articles, government documents, mass media, books and so on which are considered relevant to this research and are then analyzed using policy research. The results of the research show that digitalization of school education is important to 1) Increase Knowledge Needs 2) Improve the Quality of Student Learning; 3) equip students with four abilities: creative, communicative, critical thinking, and collaborative; 4) Supporting the government's “free learning” program, which is not limited to space and time. Digitization of school education can be used as a tool to support the virtual learning process without reducing the essence of delivering learning materials through online platforms that can be used flexibly.